Pengaruh Intensitas Emisi Karbon, Kualitas Pengendalian Internal, Insider CEO, Ukuran Perusahaan dan Ukuran Dewan Terhadap Manajemen Laba - Afidah Aulia Putri Permata; Hasnawati Hasnawati (Economic Reviews Journal, 2026)
This study aims to examine the influence of carbon emission intensity, internal control quality, insider CEO, firm size, and board size on earnings management. This study was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period, selected using a purposive sampling technique. This study uses a panel data regression analysis method with an unbalanced panel data type, which includes 45 companies with a total of 128 observations. The results of the study show that carbon emission intensity and board size have a negative influence on earnings management, while internal control quality, insider CEO and firm size have a positive influence on earnings management.